Prevalence and molecular analyses of extended spectrum β-lactamase producing uropathogens among pregnant women, Jigawa state, Nigeria - Eze L Chinyere; Sani M Nura; Gumel M Ahmad; Amoo F Kemi; Mujahid N Sani (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2020)
The Extended Spectrum β-Lactamase (ESBL)-producing uropathogens are of serious clinical concern worldwide. They are plasmid-mediated enzymes that are capable of hydrolysing virtually all β-lactam antibiotics including oxyimino-cephalosporins and monobactams. In this study, the uropathogens and risk factors for Urinary Tract Infections (UTI), their antibiotic susceptibility patterns, and plasmid studies of ESBL-producing uropathogens prevalent in pregnant women attending to Rasheed Shekoni Teaching Hospital (RSTH) and Dutse General Hospital (DGH) were investigated. During the current work, midstream urine samples were collected aseptically from 200 pregnant women and then cultured. The antibiotic susceptibility testing and ESBL detection were done using the standard methods. Identification of the recovered bacterial pathogens were carried out using the standard procedures and then confirmed through molecular analyses. The prevalence of UTI and ESBL production in this study was 37.0% and 17.6%, respectively. In pregnant women, the prevalence of UTI was higher in DGH (27.0%) than in RSTH (10.0%). The most predominant isolated uropathogens were Alcaligenes sp. (58.1%) followed by Klebsiella pneumoniae (28.3%). The most sensitive antibiotic was ceftazidime (31.2%). Molecular enumeration using 16S rRNA partial sequencing revealed the presence of 750bp .There is an urgent need to enlighten the pregnant women on the hazardous effects of self-medication, over-the-counter prescription, possible risk factors of UTI and the importance of personal hygiene during antenatal clinic, in order to prevent the emergence and spread of antibiotic resistant bacteria.